1997
DOI: 10.1176/ajp.154.8.1047
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate gyrus volume and glucose metabolism in autistic disorder

Abstract: T he importance of the anterior cingulate gyrus for autism is suggested by three lines of evidence. 1) The anterior cingulate gyrus has been implicated in higher cognitive functions and in the expression and recognition of affect-functions that are compromised in autism. 2) Increased cell densities in many areas of the limbic system, including the anterior cingulate gyrus, have been found in postmortem studies of autistic patients (1). 3) Previous positron emission tomography (PET) studies (2, 3) suggested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…ACG region plays important role in the pathophysiology of autism as shown by previous reports [26], [27]. Our positron emission tomography studies had shown that a reduction in SLC6A4 binding in the cingulate cortices is associated with an impairment of social cognition in autistic subjects [19].…”
Section: Discussionsupporting
confidence: 69%
“…ACG region plays important role in the pathophysiology of autism as shown by previous reports [26], [27]. Our positron emission tomography studies had shown that a reduction in SLC6A4 binding in the cingulate cortices is associated with an impairment of social cognition in autistic subjects [19].…”
Section: Discussionsupporting
confidence: 69%
“…Whereas the posterior cingulate cortex (PCC) is believed to play a role in visuospatial and memory function, the anterior cingulate cortex (ACC) primarily appears to be involved in the integration of affect, cognition, and behavioral expression. Haznedar et al (1997) recorded significantly smaller ACC volume in adults with autism in comparison to healthy controls.…”
Section: Resultsmentioning
confidence: 77%
“…This finding is also in good agreement with previous studies in autistic patients using metabolic or haemodynamic correlates of resting neuronal function. Reduced metabolism in the thalamus, fronto-cortical regions and ventral (but not dorsal) striatum have been described in adult patients [7], [75]. Similarly, robust and widespread reduction in cortical perfusion have been observed in young [5], [6], [76][79] and adult [78] autistic patients, with a predominant involvement of the prefrontal, cingulate, insular and temporal cortex.…”
Section: Discussionmentioning
confidence: 96%